Acquired Elliptocytosis as a Manifestation of Myelodysplastic Syndrome Associated with Deletion of Chromosome 20q - Sukesh Manthri; Naresh K. Vasireddy; Sindhura Bandaru; Swati Pathak (Case Reports in Hematology)
Elliptocytosis is commonly seen as a hereditary condition. We present a case of myelodysplastic syndrome (MDS) del(q20) variant with concomitant acquired elliptocytosis. A 73-year-old male with a history of prostate cancer presented to the hospital for evaluation of bleeding gums. Initial evaluation showed Hgb of 9.3 gm/dl, hematocrit of 28%, platelet count of 36,000 K/cmm, and WBC of 1.8 K/cmm with an ANC of 0.8 K/cmm. A slightly elevated bilirubin of 1.2 mg/dl spurred a hemolytic workup. Peripheral smear showed frequent elliptocytes, teardrop cells, schistocytes, and occasional spherocytes. Bone marrow biopsy did not show significant fibrosis to explain the elliptocytosis. Cytogenetics showed 20q deletion, and later, he was started on therapy for intermediate risk MDS. Bone marrow biopsy after completion of 6 cycles showed complete cytogenetic remission with significant improvement in elliptocytosis. Elliptocytosis in the setting of MDS has rarely been reported, and association with 20q deletion is even rarer. Animal studies have shown that haploinsufficiency of L3MBTL1 contributes to some (20q−) myeloproliferative neoplasms and myelodysplastic syndromes by affecting erythroid differentiation. Our case report raises interesting questions: Does MDS with rarely reported elliptocytosis indicate a disease process that is different from the usual 20q deletion? Is haploinsufficiency of L3MBTL1 responsible for this manifestation?